The Principles of the Spatial and Time Organization of the Autobiographical Works by Günter Grass (Proceedings of Southern Federal University. Philology, 2018)
Natalia V. Sklyar (Lugansk, Taras Shevchenko National University)The peculiarities of chronotope of the autobiographical novels are studied. The special attention is paid to the specificity of spatial time continuum of modern German autobiography. The analysis is based on Günter Grass’s autobiographies: «Peeling the Onion» and «The Box». Among the main principles of spatial time organization in these novels are singled out the text fragmentariness, inconsistent associative change of places of events, the play with forms of past and present times. The role of autobiographical memory is singled out during the description of time and place of an event. Also the specificity of the term «the fourth time» is studied as the literary method of transmission of events march and comparison of different time conditions.Key words: German autobiography, space, time, fragmentariness, autobiographical memory.